PENGARUH MODEL PEMBELAJARAN.KOOPERATIF TIPE THINK TALK WRITE TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS VIII - Fentri, Egi Wahyuni (Departemen Matematika, 2023)
Communication skills has an important position in mathematics learning, because of the skill in explaining ideas verbally or in writing. If students are good at this skill, they will be able to understand the problem correctly. However, in practice, this ability is still relatively low among students in class VIII of SMP Negeri 2 Padang. One solution to support the growth of these skills is to use the Think Talk Write (TTW) collaborative learning model. The aim of the research was to see whether this skill increases when implemented TTW in clas VIII SMP Negeri 2 Padang. Type of research is a quasi-experimental study without an appropriate post hoc pure control group. Use of mathematical communicative competence test equipment and descriptive quizzes. Data analysis shows that classroom learning using the TTW model outperforms in-person learning. and experienced a significant increase. Keywords–Cooperative Learning, Direct Learning, Mathematical Communication Skills, Think Talk Write .